Ag Nanoparticle-Decorated SiO2–Al2O3–ZrO2 Composites as a Low-Cost Substrate for Enhanced Signal Infrared Spectroscopy - Reyes-López, Simón Yobanny (2024)
A ceramic-metal composite was produced by using the sol–gel method and the electrospinning technique as a potential enhancement substrate for infrared spectroscopy. The precursor solution of tetraethyl orthosilicate, aluminum nitrate, and zirconium butoxide was mixed with polyvinylpyrrolidone and then electrospun into nonwoven fibrous membranes. The membranes were sintered, decorated with silver nanoparticles, and characterized by using scanning electron microscopy (SEM), X-ray diffraction (XRD), and attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR). The ceramic membranes were composed of cylindrical fibers with an average diameter of ∼190 nm with a smooth surface and spherical particles with an average diameter of ∼9 nm embedded evenly on top. The enhancement capacity of the substrates was tested using pyridine at different concentrations with infrared spectroscopy. An enhancement factor of approximately 1 × 106 times for the signal of pyridine 1 nM was achievable, showing the material is a promising alternative to a low-cost nanostructured surface enhancement substrate for infrared spectroscopy.